Visual Information Communication - Huang, Mao Lin; Nguyen, Quang Vinh; Zhang, Kang (Springer US : Imprint: Springer, 2010)
Visual Information Communication is based on VINCI'09, The Visual Information Communications International Conference, September 2009 in Sydney, Australia. Topics covered include The Arts of Visual Layout, Presentation & Exploration, The Design of Visual Attributes, Symbols & Languages, Methods for Visual Analytics and Knowledge Discovery, Systems, Interfaces and Applications of Visualization, Methods for Multimedia Data Recognition & Processing. This cutting-edge book addresses the issues of knowledge discovery, end-user programming, modeling, rapid systems prototyping, education, and design activities. Visual Information Communications is an edited volume whose contributors include well-established researchers worldwide, from diverse disciplines including architects, artists, engineers, and scientists. Visual Information Communication is designed for a professional audience composed of practitioners and researchers working in the field of digital design and visual communications. This volume is also suitable for advanced-level students in computer science.